По прозвищу Ворон. Закон мести: [роман] / Валерий Горшков - Горшков Валерий Сергеевич (АСТ-ПРЕСС, 1999)
Экземпляры: аб. (2008) / Инвентарный номер: 52141 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Г 70 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44